(untitled) - Brenan, Gerald (Cambridge,New York, 1990)
Gerald Brenan's The Spanish Labyrinth has become the classic account of the background to the Spanish Civil War. Written during and immediately after the Civil War, the book has all the vividness of the author's experience. It represents a struggle to see the issues in Spanish politics objectively, whilst bearing witness to the deep involvement which is the only possible source of much of this richly detailed account. As a literary figure on the fringe of the Bloomsbury group, Gerald Brenan lends to this narrative an engaging personal style that has become familiar to many thousands of readers over the decades since it was first published
Keywords: Lịch sử Tây Ban Nha,Lịch sử Tây Ban Nha; Giai đoạn 1886-1931,1931-1939